Association between Interleukin-21 and Interleukin-21 receptor gene polymorphisms with susceptibility to chronic hepatitis B virus infection and HBV spontaneous clearance in Iranian population. (March 2019) - Shoraka, Shahrzad; Mohebbi, Seyed Reza; Hosseini, Seyed Masoud; Hosseini Razavi, Armin; Hatami, Yasin; Sharifian, Afsaneh; Rostami-Nejad, Mohammad; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza
Abstract: Hepatitis B virus (HBV) infection is a major public health concern due to the infection often leads to chronic infection, liver cirrhosis and also liver cancer. The host immune response to HBV infection and also genetic background play significant role in outcome of infection. Single nucleotide polymorphisms (SNPs) are the most important kind of variation in genetic sequences that caused by point mutations. As cytokines have major roles in viral infections, it seems that cytokine gene polymorphisms are independently associated with response to viral infections. Interleukin 21 (IL-21) plays an influential role in both innate and adaptive immune responses. Its specific receptor, IL-21R, produced and located on the surface of T, B and natural killer (NK) cells and is critical for the proliferation and differentiation of these immune effector cells. Many studies confirmed that the IL-21 involved in response to viral infections. We aimed to investigate the association of G/T IL-21 (rs2055979) and C/T IL-21R (rs3093390) gene polymorphisms with chronic hepatitis B virus infection and HBV spontaneous clearance in Iranian population. Methods: In this study, blood samples were gathered from 320 patients with chronic HBV and 310 healthy controls and also 120 HBV spontaneous clearance individuals. Following genomic DNA extraction, genotypes of the selected SNPs determined by PCR and restriction fragment length polymorphism (RFLP) method. The results were analyzed by SPSS software using Chi-square, Logistic Regression, ANOVA and Independent Samples t -Test. Results: According to our results, in IL-21R (rs3093390 C/T) gene polymorphism, allele frequency of T is statistically different in the HBV spontaneous clearance group compared to chronic HBV cases. But there is no significant difference between G/T IL-21 (rs2055979) and C/T IL-21R (rs3093390) genotypes distribution in three groups. Also we found that higher serum aspartate transaminase (AST) level in HBV spontaneous clearance group is significantly associated with TT genotype of IL-21 (rs2055979) compared to GG genotype (P value = 0.006). Discussion: Our results showed that T allele frequency in IL-21R (rs3093390 C/T) gene polymorphism could consider as a host genetic factor for HBV spontaneous clearance. Probably we can serve it as a potential prognostic genetic marker for spontaneous clearance of HBV infection. Highlights: T allele frequency in IL-21R (rs3093390 C/T) gene polymorphism was higher in HBV spontaneous clearance group. T allele frequency in IL-21R gene polymorphism might be consider as a host genetic factor for HBV spontaneous clearance. T allele frequency may serve as a potential prognostic genetic marker for spontaneous clearance of HBV.